Extracellular signal‐regulated kinase 2 has duality in function between neuronal and astrocyte expression following neonatal hypoxic–ischaemic cerebral injury. (11th July 2018) - Thei, Laura; Rocha‐Ferreira, Eridan; Peebles, Donald; Raivich, Gennadij; Hristova, Mariya
Abstract : Key points: This study identifies phosphorylated extracellular signal‐regulated kinase (ERK) to be immediately diminished followed by a rapid if transient increase for up to 4 h following hypoxic–ischaemic insult (HI) in the neonatal mouse. Phosphorylated ERK up‐regulation was prevented with systemic injection of the mitogen‐activated protein kinase kinase (MEK) inhibitor SL327. Treatment with SL327 both pre‐ and post‐HI gave a strong reduction in the number of dying cells and microgliosis. By utilising transgenic mouse mutations, we observe that neuronal ERK2 significantly contributes to tissue damage, while ERK1 and astrocytic ERK2 are neuroprotective. Compared to global inactivation, selective cell‐specific interference with ERK activity could result in stronger neuroprotection. Abstract: Hypoxia–ischaemia (HI) is a major cause of neonatal brain injury resulting in cerebral palsy, epilepsy, cognitive impairment and other neurological disabilities. The role of extracellular signal‐regulated kinase (ERK) isoforms and their mitogen‐activated protein kinase kinase (MEK)‐dependent phosphorylation in HI has previously been explored but remains unresolved at cellular level. This is pertinent given the growing awareness of the role of non‐neuronal cells in neuroprotection. Using a modified Rice–Vannucci model of HI in the neonatal mouse we observed time‐ and cell‐dependent ERK phosphorylation (pERK), with strongly up‐regulated pERK immunoreactivity first in periventricular white matter axons within 15–45 min of HI, followed by forebrain astrocytes and neurons (1–4 h post‐HI), and return to baseline by 16 h. We explored the effects of pharmacological ERK blockade through the MEK inhibitor SL327 on neonatal HI‐brain damage following HI alone (30 or 60 min) or lipopolysaccharide (LPS)‐sensitised HI insult (30 min). Global inhibition of ERK phosphorylation with systemically applied SL327 abolished forebrain pERK immunoreactivity, and significantly reduced cell death and associated microglial activation at 48 h post‐HI. We then explored the effects of cell‐specific ERK2 deletion alone or in combination with global ERK1 knockout under the same conditions of HI insult. Neuronal ERK2 deletion strongly decreased infarct size, neuronal cell death and microglial activation in grey matter following both HI alone or LPS‐sensitised HI. ERK1 deletion attenuated the protective effect of neuronal ERK2 deletion. Removal of astroglial ERK2 produced a reverse response, with a 3‐ to 4‐fold increase in microglial activation and cell death. Our data suggest a cell‐specific and time‐dependent role of ERK in neonatal HI, with a predominant, neurotoxic effect of neuronal ERK2, which is counteracted by neuroprotection by ERK1 and astrocytic ERK2. Overall, global pharmacological inhibition of ERK phosphorylation is strongly neuroprotective. Key points: This study identifies phosphorylated extracellular signal‐regulated kinase (ERK) to be immediately diminished followed by a rapid if transient increase for up to 4 h following hypoxic–ischaemic insult (HI) in the neonatal mouse. Phosphorylated ERK up‐regulation was prevented with systemic injection of the mitogen‐activated protein kinase kinase (MEK) inhibitor SL327. Treatment with SL327 both pre‐ and post‐HI gave a strong reduction in the number of dying cells and microgliosis. By utilising transgenic mouse mutations, we observe that neuronal ERK2 significantly contributes to tissue damage, while ERK1 and astrocytic ERK2 are neuroprotective. Compared to global inactivation, selective cell‐specific interference with ERK activity could result in stronger neuroprotection.